Digitally Programmable Integrator and Differentiator - Abdulrahman Khalaf Al-Ali; Muhammad Taher Abuelma'atti; Syed Yunus (Active and Passive Electronic Components)
Digitally programmable integrator and differentiator circuits are presented. Each circuit uses at most one operational amplifier, two operational transconductance amplifiers, and one capacitor. The time constants of the circuits are decided by the biasing currents of the operational transconductance amplifiers. The circuits can be easily interfaced with microprocessor-based systems. Experimental results are included.